From discourse to writing: the memory of Brazilian National Rap as an effect of resistance - de Sousa Bandeira, Ana Luiza; Almeida Ruiz, Marco Antonio (Revista Letras Raras, 2024)
This article aims to analyze the effects of resistance emerging from three songs in Brazilian national rap: “Pânico na Zona Sul” (1989) by Racionais MC’s, “Cidadão Comum Refém” (2002) by Mv Bill, and “Favela Vive 4” (2020) by ADL. More specifically, we seek to understand how the lyrics of these songs contribute not only to the popularization of Brazilian culture but also constitute spaces of resistance and denunciation for minority groups placed “on the margins” by a portion of society, as they represent environments that reinforce dominant spaces imbued with social stigmas and visually represented by negative stereotypes (“poor”, “slum dwellers”, among others), attributions primarily assigned to the black community. The material chosen consists of three songs from three different decades, each with certain regularities that represent the current configuration of Brazil's social reality. In this context, we analyze the excerpts beyond their well-known musical genre, observing them as instruments of resistance embodied in the verses, thus contributing to the denunciation of the segregation of this community. Through French discourse analysis, we aim to understand rap as a discursive event that redefines the entire memory of resistance among blacks and the poorest in different spheres of Brazilian society, placing them in a significant and necessary space of redefinition.